Characterization of commercial green tea leaves by the analysis of low molecular weight carbohydrates and other quality indicators. (30th August 2019) - Megías-Pérez, Roberto; Shevchuk, Anastasiia; Zemedie, Yeweynwuha; Kuhnert, Nikolai
Highlights: Extended quantitative study of the main LMWC in a large set of 56 commercial green teas. Changes observed in the indicators evaluated depend on processing conditions. PCA was employed to evaluate differences between samples based on processing. HCA was employed to explore similarities between samples based on origin. Abstract: A comprehensive characterization of commercial green tea (CGT) with the employment of independent variables such as low molecular weight carbohydrates (LMWC), soluble solids, color and antioxidant capacity has been performed in this manuscript. Within the manuscript, a convenient HILIC-MS method, suitable to perform a simultaneous identification and quantification of all mono-, di-, oligosaccharides and cyclitols observed in green tea was introduced. The method covers all key analytes in a single chromatographic analysis. Fifty-six samples from different origins (n = 10) were evaluated to explore differences based on origin. In addition, commercial samples processed by pan-firing and steaming were used for comparative purposes, allowing the identification of putative processing markers. The results obtained contribute to gain a better knowledge of the variations, according to origin and processing, in composition and quality of CGT, commodity widely appreciated by the consumers.